“Distinguished” Women Entrepreneurs in the Digital Economy and the Multitasking Whirlpool - Irene Kamberidou (Journal of Innovation and Entrepreneurship, Springer Open, 2020)
How are women entrepreneurs transforming and challenging traditional understandings of professional success in the 21st century, despite the multitasking whirlpool? What type of knowledge and skills are required in today's digital world to develop professionally and succeed as an entrepreneur? What are the major barriers to successful entrepreneurship preventing women from realizing their full potential or stopping them from even beginning an entrepreneurial career? A current literature review (2011-2019) on women's entrepreneurial initiatives, skills, characteristics, attributes, motives and leadership styles, documenting strategies for success and barriers confronted, indicates that not much has changed. Women entrepreneurs continue to face the multitasking whirlpool, along with the lack of financial resources, marketing skills and support services, including poor access to business networks, technology and digital markets. Despite the mass entry of women in exclusively male domains, glass ceilings have not been shattered. Then again, developed and developing nations have come to understand that women's entrepreneurial activities contribute to socioeconomic growth and utilizing the full potential of all human resources is essential for sustainable development. Studies of the 21st century-as those of the late 20th century-continue to spotlight gender gaps in entrepreneurship as well as the so-valued career-family balance, while still arguing that further research is needed. They also agree that successful entrepreneurship requires digital skills along with the drive for innovation. The successful entrepreneur, or to use a term and concept coined by Elias G. Carayannis and McDonald R. Stewart (2013), the "distinguished entrepreneur" regardless of gender, is an innovator; a visionary; a person who predicts and shapes the future; takes initiatives; accepts change, risk and failure; learns from it; and sees what others do not see, among other things. Accordingly, this study presents snapshots of lives changed and empowered. It includes the work and narratives of "distinguished" (Carayannis & Stewart 2013) women entrepreneurs who have made a difference. Is it not time to shed some light on inspirational role models, especially those who are excelling in the startup world, the Blue Economy and the Silver Economy? KEYWORDS: Women, Entrepreneurship, Multitasking whirlpool, Gender participation gap, Gender pay gap, Gender leadership gap, Work–life balance, Digital skills, Degendering